Learning Maharah Qira'ah and Kitabah in Syarqi Markaz Arabiyah Pare Kediri Class - Sari, Devi Rafika; Arsandi, Arsandi; Wahhab, Abdul; Hilmi, Danial (Borneo Journal of Language and Education, 2022)
The purpose of this study was descript learning maharah qira'ah and maharah kitabah are taught in the Syarqi markaz Arabiyah Pare Kediri class, the research method used is a qualitative approach with descriptive analysis. The research instruments in this study were observation and documentation. The results of the study show that first, the target of maharah qira'ah learning in the Syarqi Tsani class is to be able to read texts fluently, that is, in accordance with their qawaid, be able to translate words, and understand the meaning of the text as a whole. When viewed from its level, this qira'ah learning is an advanced level, and the learning method used is the discussion method. Second, the target of Maharah Kitabah learning in the Syarqi Awwal class is to write correctly. When viewed from the level, it is the level of mubtadi'. The method used is the questioning method (question and answer).